Development and Validation of Novel UV Spectrophotometric Method for the Determination of Evogliptin Tartarate in Pharmaceutical Dosage Form - Agrawal, Yogesh Purushottam; Agrawal, Mona Yogesh; Jadhav, Siddhesh Bharat; Shinde, Renuka Jagannath (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: Development of a novel precise, selective and sensitive UV spectrophotometric method for the estimation of Evogliptin tartarate in bulk and tablet dosage forms. Materials and Methods: The estimation was carried out using deionized water as solvent and Quantitation was achieved using double beam UV spectrophotometer at 267 nm. Results: The Calibration curves of Evogliptin tartarate shows good linearity over the concentration range from 10-100 μg/mL with excellent correlation coefficient (R2=0.992). The percent relative standard deviation < 2.0 % confirmed the precision of the method. Excellent recovery (98.86 to 99.51) with low percent relative error proved the accuracy of method. The specificity of the methods was analyzed by evaluating marketed pharmaceutical formulation of Evogliptin tartarate. Conclusion: In the present work we report for the first time, a UV-spectrophotometric method for the analysis of Evogliptin tartarate and the proposed method showed excellent sensitivity, selectivity and linearity as per ICH Q2 (R1) guidelines. In addition the effectiveness of the developed method was demonstrated with marketed pharmaceutical formulation reflects good recovery percentage. It is evident that the proposed method will serve as a standard protocol for routine analysis of Evogliptin tartarate in bulks, Pharmaceutical formulations and would be of great help to Pharmaceutical industries in the future.
Keywords: Evogliptin tartarate; UV-Spectrophotometry; Pharmaceutical formulations; Analytical Method Development; Validation